Influence of Cu, Si, and Ni and thermal parameters of solidification on the mechanical properties and microstructure in Al-based hypoeutectic alloys (Research, Society and Development, 2024)
The objective of the work is to carry out an experimental investigation of the effects of solutes on the microstructure and mechanical properties in the upward unidirectional solidification of hypoeutectic binary aluminum alloys under transient heat extraction conditions. As well as generating empirical mathematical models to contribute to the development of solidification processes and their products. Using a quantitative, experimental, and laboratory methodology, cooling curves were plotted, which allowed for the determination of thermal parameters such as cooling rate, solidification speed, thermal gradient, and local solidification time. The Al-Cu alloy has higher thermal conductivity; therefore, it presented superior experimental results of thermal parameters when compared to the Al-Si and Al-Ni alloys. Experimental laws of microstructural development were also determined, associating dendritic spacing with the positions of thermocouples, microhardness and modulus of elasticity. Thus, the dependence of microhardness on primary dendritic spacings and on solutes is inferred. On the other hand, the spacing between the primary arms apparently does not affect the modulus of elasticity. Nevertheless, there was a considerable increase in the modulus of elasticity values with the Al-5 wt.% Ni alloy, around 120% over the Al-5 wt.% Cu alloy and 18% over the Al-5 wt.% Si.